Deposition of MoSe2 flakes using cyclic selenides - Charvot, Jaroslav; Zazpe, Raul; Krumpolec, Richard; Rodriguez Pereira, Jhonatan; Pavliňák, David; Pokorný, Daniel; Klikar, Milan; Jelínková, Veronika; Macák, Jan; Bureš, Filip (ROYAL SOC CHEMISTRY, 2021)
The currently limited portfolio of volatile organoselenium compounds used for atomic layer deposition (ALD) has been extended by designing and preparing a series of four-, five- and six-membered cyclic silylselenides. Their fundamental properties were tailored by alternating the ring size, the number of embedded Se atoms and the used peripheral alkyl chains. In contrast to former preparations based on formation of sodium or lithium selenides, the newly developed synthetic method utilizes a direct and easy reaction of elemental selenium with chlorosilanes. Novel 2,2,4,4-tetraisopropyl-1,3,2,4-diselenadisiletane, which features good trade-off between chemical/thermal stability and reactivity, has been successfully used for gas-to-solid phase reaction with MoCl5 affording MoSe2. A thorough characterization of the as-deposited 2D MoSe2 flakes revealed its out-of-plane orientation and high purity. Hence, the developed four-membered cyclic silylselenide turned out to be well-suited Se-precursor for ALD of MoSe2.
Depozice MoSe2 s použitím cyklických selenidů
Keywords: atomic layer deposition; selenide; depozice atomárních vrstev; selenidy